Children - Santos, Luisa Micaela Teixeira (2018)
Modern society is being marked by conflict, wars, socioeconomic imbalances, violence, poverty, hunger, exploitation, forcing forced migration across borders. According to the United Nations, in 2017, all around the world, 68.5 million people were forced to abandon their assets for reasons of survival. For this reason, as a result, Europe is receiving an unprecedented influx of asylum seekers. This forced migration has a high impact on the physical and mental health of adults and children. The latter are the ones who suffer the most from displacement, that's why the mental health of children is on the agenda of international organizations. According to the International Council of Nurses, nurses are a key factor in the health responses to these populations, especially in the area of mental health. Therefore, this study aims to study the vulnerability and protective factors in mental health of asylum seeking children living in a refugee camp. The study of these factors is essential for the construction of specific mental health promotion programs that can be implemented by specialist nurses. A qualitative, exploratory and descriptive study carried out in the Refugee Camp of Kara Tepe, Island of Lesbos, Greece. It includes a data collection integrated in the ethnographic method, including participant observation and semistructured interviews. The sample of 8 people included included education professionals, volunteers and children over 15 years of age residing in the Kara Tepe Refugee Camp, with legal authorization from legal representatives. The data were transcribed, translated and analyzed through thematic inductive analysis. Asylum-seeking children living in Kara Tepe have a higher number of negative conditioning factors as a result of the multiple and simultaneous transitions they are experiencing. For this reason, some already present mental suffering and others have a high probability of developing mental health disorders. Mental health nurse can provide appropriate interventions to assist these children and their families in acquiring skills to help them incorporate new knowledge and change behaviors in order to cope with the transitional situation